Uso de veículo aéreo não tripulado para monitoramento e auxílio de medições de obras de pavimentação urbana - Furtado, Ryan de Araujo (Universidade Federal Rural do Semi-Árido, 2021)
Construction of urban pavement is an essential element are an essential element for the proper functioning and development of cities, being considered commonplace in any municipality in the country. Being able to control and measure these works efficiently and transparently is a crucial aspect of public management, since financial resources from taxes collected from taxpayers are invested in them. In order to make the process of inspection of works more efficient, this research aimed to test and evaluate the feasibility of using Unmanned Aerial Vehicles (UAV's) to measure public paving works, as an alternative to the traditionally used method. The present work was developed from a case study that analyzed the execution of paving services in 4 streets in the city of Mossoró-RN, applying the traditional methodology (direct measurements obtained in the field) and the alternative methodology, using a UAV. The length, width and area obtained by the two methods were compared, and the estimated time taken to perform the measurements. The use of Unmanned Aerial Vehicles (UAV's) to measure urban paving works proved to be a viable technique. Compared to the method traditionally used, it presented advantages such as greater productivity in surveying areas, less time spent on surveying and measuring, in addition to enabling more secure storage of collected information, resulting in more efficiency and transparency in the control of public works. Thus, it is suggested that further research be carried out in order to standardize the methods and procedures used for surveying and measuring works, in addition to disseminating these techniques to public administrators across the country
Keywords: Inspeção de pavimentos; Fiscalização de obras pública; Drones; Pavement Inspection; Inspection of Public Works; Drones; ENGENHARIAS::ENGENHARIA CIVIL